Sri Lanka : Accounting and Auditing - World Bank (Washington, DC, 2013)
Sri Lanka has made considerable efforts in aligning its accounting and auditing practices with international standards to establish a high-quality corporate financial reporting system. Corporate accounting and disclosure practices, particularly for publicly traded companies, have improved over the past decade. Among forward-looking actions has been the enactment of the Sri Lanka Accounting and Auditing Standards Act and establishment of the Sri Lanka Accounting and Auditing Standards Monitoring Board. However, there appears to be a certain degree of noncompliance in both accounting and auditing practices, resulting mainly from weak enforcement. The weakness is primarily attributed to inadequate regulatory capacity. This report provides an appraisal of the accounting and auditing practices within a broader context of the Sri Lanka institutional framework, and the capacity needed to ensure high-quality corporate financial reporting. Building on past achievements, comprehensive efforts are necessary for strengthening the capacity of regulators, and ensuring effective coordination. Also, there is an urgent need for a system of independent oversight of the audit profession that will protect public interest. This report provides a wide range of policy recommendations focusing on building regulatory capacity, strengthening enforcement mechanisms, initiating legal reforms, undertaking awareness programs for shareholders and top management, urging compliance with guidelines of the International Federation of Accountant, improving education and training, introducing independent oversight of the audit profession, strengthening the professional association, publicizing more widely the enforcement actions against non-compliances, upgrading the licensing procedures for accountants and practicing auditors, and, disclosing audit and non-audit fees separately. These recommendations are expected to provide inputs for designing a country action plan that will further improve the accounting and auditing regime of Sri Lanka.